SISTEM INFORMASI INVENTORY ALAT TULIS KANTOR (ATK) MENGGUNAKAN METODE WATERFALL (STUDI KASUS : OTORITAS JASA KEUANGAN (OJK)) - Karlena Indriani; Sudarmadi Sudarmadi (Jurnal Techno Nusa Mandiri, 2015)
Management Systems ATK (Stationery Office tools) in the Financial Services Authority ( FSA ) is currently still done manually, thus still frequent occurrence of error information. With this information errors, report creation has slowed plans for the use of goods budget submission next year. How the management of inventory data can be integrated with both the master data, transaction data, and reports? How to design a system that can give information about the classification code of the goods so as to facilitate the administration of the Head in managing data items? How to design a system that can provide a warning when approaching the limit stock inventory minimum? How Kasubag can obtain information in the form of a complete report as required in the master data and transaction data each period? Intranet-based information systems that can provide information on the activities demand ATK (Stationery Office Tools) from each directorate or department. Creating a management information system design stationery that is expected to assist and speed up the reporting process and reduce errors ATK usage information that will generate reports that can be accounted for